After dark : the nocturnal urban landscape and lightscape of ancient cities - Gonlin, Nancy; Strong, Meghan E. (Louisville, Colorado : University Press of Colorado, 2022)
"After Dark explores the experience of nighttime within ancient urban settings. Contributors present evidence related to how ancient people manipulated and confronted darkness and night in urban landscapes, advancing our knowledge of the archaeology of cities, the archaeology of darkness and night, and lychnology (the study of ancient lighting devices)"--
Front Matter -- Contents -- Figures and tables -- Preface -- City nights -- Looking for light in ancient egyptian urban rituals -- Danger in the mesopotamian night -- Illuminating the mysteries of the great gods at samothrace, greece -- Living landscapes of night in tiwanaku, bolivia -- Lunar power in ancient maya cities -- Every day hath a night -- Cahokia after dark -- Notes on the chacoan nightscape -- The aztec new fire ceremony and the illumination of the night -- Nocturnal urban landscapes -- Index -- Contributors
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 01, 2022).
JSTOR
Keywords: Cities and towns, Ancient; Municipal lighting -- History; City and town life -- History; Lighting -- Social aspects; Night -- Social aspects; Sociology, Urban; Villes antiques; Éclairage public -- Histoire; Vie urbaine -- Histoire; Nuit -- Aspect social; Sociologie urbaine; urban sociology; SOCIAL SCIENCE / Archaeology; SOCIAL SCIENCE / General; Cities and towns, Ancient; City and town life; Lighting -- Social aspects; Municipal lighting; Night -- Social aspects; Sociology, Urban; Electronic books; History